Studies of K−-nuclei interactions at low-energies by AMADEUS. (December 2020) - Del Grande, R.; Bazzi, M.; Bragadireanu, A. M.; Bosnar, D.; Cargnelli, M.; Clozza, A.; Curceanu, C.; De Paolis, L.; Fabbietti, L.; Ghio, F.; Guaraldo, C.; Iliescu, M.; et al.
Abstract: The AMADEUS collaboration is providing unique experimental information on the low-energy strong interaction between K − and nucleons exploiting the low momentum K − (pK ∼ 127 MeV/c) produced at the DAΦNE collider and using the KLOE detector as active target. The absorption of the K − in light nuclei (H, 4 He, 9 Be and 12 C) are investigated and hyperon-pion/hyperon-nucleons, emitted in the final state, are reconstructed. In the present work the results obtained from the study of Λπ −, Ap and At correlated production will be presented.